2021
DOI: 10.3892/ol.2021.12714
|View full text |Cite
|
Sign up to set email alerts
|

Daphnoretin induces reactive oxygen species‑mediated apoptosis in melanoma cells

Abstract: Research suggests that daphnoretin exhibits a diverse array of antitumor mechanisms and pharmacological activities. However, there is no definitive explanation for the antitumor mechanisms of daphnoretin in malignant melanoma. In the present study, MTT and colony formation assays demonstrated that daphnoretin significantly inhibited the proliferation of melanoma A375 and B16 cells. Following treatment with daphnoretin, apoptotic bodies were observed in A375 and B16 cells via Hoechst 33258 staining. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Regarding daphnoretin, it has been mentioned that much of the research on this compound focuses on its anticancer activity. For example, in a recent report (2021), its ability to induce mitochondrial apoptosis and inhibit the proliferation of human (A375) and mouse (B16) malignant melanoma cells was shown through the activation of the production of reactive species of oxygen (ROS) [30] . Also, in 2007 daphnoretin (1.875, 3.75, 7.5, and 15 mg kg −1 ) administered orally to mice showed to cause the animals to spend more time in the open arms of an elevated plus maze, indicating that this coumarin has effects on the central nervous system that is manifested as a decrease in anxiety‐like behavior [8]…”
Section: Resultsmentioning
confidence: 99%
“…Regarding daphnoretin, it has been mentioned that much of the research on this compound focuses on its anticancer activity. For example, in a recent report (2021), its ability to induce mitochondrial apoptosis and inhibit the proliferation of human (A375) and mouse (B16) malignant melanoma cells was shown through the activation of the production of reactive species of oxygen (ROS) [30] . Also, in 2007 daphnoretin (1.875, 3.75, 7.5, and 15 mg kg −1 ) administered orally to mice showed to cause the animals to spend more time in the open arms of an elevated plus maze, indicating that this coumarin has effects on the central nervous system that is manifested as a decrease in anxiety‐like behavior [8]…”
Section: Resultsmentioning
confidence: 99%
“…It has multiple pharmacological effects of antitumor. Previous studies have found that Daphnoretin could inhibit the proliferation, migration and viability of colon cancer cells [ 11 ], malignant melanoma cells [ 12 ], lung cancer cells [ 13 ] and cervical cancer cells [ 14 ] in vitro . And it can regulate the differentiation and maturation of DCs by mediating p-JUk activity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…C. A. Meyer), belonging to the Wikstroemia genus of the Thymelaeaceae family, was a traditional Chinese medicine, reporting with a variety of antitumor active compounds such as daphnoretin (DAP) (Shao et al, 2020;Shi et al, 2021). DAP, a dicoumarin derivative, could inhibit various cancer cell growth, especially inducing HCC apoptosis via an increase in Bax and p53 expression and a decrease in Bcl2 expression (Yu et al, 2019;Badawy et al, 2021;Wang et al, 2021;Yao et al, 2021). However, DAP exhibited low water solubility and rapid clearance from the bloodstream, thus resulting in a short T1/2 in the plasma (3.5 h) (Hu et al, 2017;Liang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%